Prevalence of vitamin D deficiency in patients with spinal cord injury at admission: a single-centred study in the UK. (20th February 2023) - Wong, Samford; Dong, Honglin; Hirani, Shashivadan P.; Gainullina, Irina; Ussef, Ibrahim; Graham, Allison
Abstract: Vitamin D deficiency is prevalent in patients with chronic spinal cord injury (SCI) and has been implicated as an aetiologic factor of osteoporosis and various skeletal and extra-skeletal issues in SCI patients. Few data were available regarding vitamin D status in patients with acute SCI or immediately assessed at hospital admission. This retrospective cross-sectional study evaluated vitamin D status in SCI patients at admission to a UK SCI centre in January–December 2017. A total of 196 eligible patients with serum 25(OH)D concentration records at admission were recruited. The results found that 24 % were vitamin D deficient (serum 25(OH)D < 25 nmol/l), 57 % of the patients had serum 25(OH)D < 50 nmol/l. The male patients, patients admitted in the winter–spring time (December–May), and patients with serum sodium < 135 mmol/l or with non-traumatic causes had a significant higher prevalence of vitamin D deficiency than their counterparts (28 % males v. 11⋅8 % females, P = 0⋅02; 30⋅2 % in winter–spring v. 12⋅9 % in summer–autumn, P = 0⋅007; 32⋅1 % non-traumatic v. 17⋅6 % traumatic SCI, P = 0⋅03; 38⋅9 % low serum sodium v. 18⋅8 % normal serum sodium, P = 0⋅010). There was a significant inverse association of serum 25(OH)D concentration with body mass index (BMI) ( r = −0⋅311, P = 0⋅002), serum total cholesterol ( r = −0⋅168, P = 0⋅04) and creatinine concentrations ( r = −0⋅162, P = 0⋅02) that were also significant predictors of serum 25(OH)D concentration. Strategies for systematic screening and efficacy of vitamin D supplementation in SCI patients need to be implemented and further investigated to prevent the vitamin D deficiency-related chronic complications.